Silicon-doped hafnium oxide anti-ferroelectric thin films for energy storage - Ali, Faizan; Liu, Xiaohua; Zhou, Dayu; Yang, Xirui; Xu, Jin; Schenk, Tony; Müller, Johannes; Schroeder, Uwe; Cao, Fei; Dong, Xianlin (Journal of applied physics, 2017)
Motivated by the development of ultracompact electronic devices as miniaturized energy autonomous systems, great research efforts have been expended in recent years to develop various types of nano-structural energy storage components. The electrostatic capacitors characterized by high power density are competitive; however, their implementation in practical devices is limited by the low intrinsic energy storage density (ESD) of linear dielectrics like Al2O3. In this work, a detailed experimental investigation of energy storage properties is presented for 10 nm thick silicon-doped hafnium oxide anti-ferroelectric thin films. Owing to high field induced polarization and slim double hysteresis, an extremely large ESD value of 61.2 J/cm3 is achieved at 4.5 MV/cm with a high efficiency of ∼65%. In addition, the ESD and the efficiency exhibit robust thermal stability in 210–400 K temperature range and an excellent endurance up to 109 times of charge/discharge cycling at a very high electric field of 4.0 MV/cm. The superior energy storage performance together with mature technology of integration into 3-D arrays suggests great promise for this recently discovered anti-ferroelectric material to replace the currently adopted Al2O3 in fabrication of nano-structural supercapacitors.